Under pressure - Ody-Brasier, Amandine; Sharkey, Amanda (Strategic Management Journal, 2019)
[Research Summary:This paper examines firms' strategic responses to reputational pressures in a critical healthcare domain—the U.S. nursing home industry. We investigate whether organizations improved in terms of care quality following an exogenous change in the required number of nursing hours associated with star-based ratings to which nursing homes are subject. We show that although firms at risk of losing a star tended to self-report higher staffing levels after the policy change, these reported increases were not associated with improvements in an important patient outcome—bedsores. These findings are consistent with false reporting of staffing data, or insufficient or ineffective hiring practices. Although we cannot definitively establish the existence of false reporting, supplementary analyses offer little support for the latter two possibilities. Managerial Summary:Third-party ratings systems often stipulate that firms meet certain standards to attain a favorable evaluation. Firms must make strategic decisions about whether and how to comply with these. This paper examines firms' strategic responses to changes in the required number of nursing hours associated with star-based ratings in the nursing home industry. Our results indicate that firms at risk of losing a star responded by reporting staffing increases. However, we find no concurrent improvement in a patient outcome that previous research suggests should change as a result of increased staffing. We investigate whether the lack of improvement may be due to insufficient or ineffective hiring, and find scant evidence of either one. Although we lack direct evidence of false reporting, our findings suggest this as a strong possibility.]